Engineering practice for oilfield and drilling applications - Dareing, Don W. (John Wiley & Sons, Inc., 2022)
"Mechanical engineers design and support the plant equipment, boilers, and pressure vessels used in the oil and petroleum industries, for both onshore and offshore drilling. Their tasks include developing and monitoring the performance of mechanical systems, specifying and installing equipment, and ensuring that regulatory requirements are met. There are unique industry specifications that must be taken into account when designing in this field."-- Provided by publisher.
Keywords: Petroleum engineering.; Oil well drilling.; elektronické knihy; electronic books